STRATEGI KOMUNIKASI PEMASARAN PT BANK TABUNGAN NEGARA MELALUI MEDIA SOSIAL INSTAGRAM @BANKBTN - Alfi Yulaika (2023)
Bank BTN has not yet become the bank most widely used by the public in transactions because Bank BTN is still focused on managing mortgage products. This is a problem because a bank requires third party funds (DPK) to operate its business activities. To overcome this, one of the ways is Bank BTN need to do a marketing communication strategy that is adaptive to the times, namely through Instagram which aims to gain awareness and acquisition. This study aims to find out and understand how Bank BTN carries out marketing communication strategies on Instagram social media with AISAS Model. AISAS is a marketing model which developed by Dentsu to approach the target market according to technological developments. This study used a descriptive research method with study case approach. This study using primary data sources which were conducted using in-depth interviews and secondary data obtained from participant observation and documentation. Data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. This study uses the validity of triangulation data source techniques. The results of this study indicate that there is harmony between Bank BTN's marketing communication strategy on Instagram and the AISAS concept, which is growing audience awareness by using Instagram Ads, developing audience interest by consistenly upload soft selling content to raise public curiosity to find more information about Bank BTN and made it easy by using hashtags. Besides that, Bank BTN does not utilize digital technology in terms of service.